Perioperative Management of Craniotomy for Clipping Aneurysm: A Case Report - Damatus Try Hartanto Taopan; I Putu Pramana Suarjaya (Fakultas Kedokteran Universitas Pelita Harapan, 2026)
Background: Ruptured aneurysm is the most common cause of spontaneous subarachnoid hemorrhages. The clinical manifestations of aneurysmal subarachnoid hemorrhage are rapid onset of severe headache, loss of consciousness, nausea and/or vomiting, nuchal rigidity, or photophobia. The definitive treatment of the aneurysm is craniotomy and clipping or endovascular coiling. Several pathophysiological consequences of subarachnoid hemorrhage have been reported in previous studies. The role of the anesthesiologist is to acknowledge these sequelae in order to conduct a thorough pre anesthesia evaluation and to prepare perioperative management. However, case reports that discussed perioperative management of craniotomy for clipping aneurysm are still lacking. Case Description: We present a case of a 66-year-old woman diagnosed with acute non-communicating hydrocephalus, intraventricular hemorrhage pan-ventricle and subarachnoid hemorrhage in basal cistern, right and left sylvian fissure, right and left temporal due to aneurysm rupture post VP. Craniotomy for aneurysm clipping was planned and the surgery was done under general anesthesia. Intraoperatively, the patient’s hemodynamic was successfully maintained stable. Conclusion: Postoperatively, patient was closely monitored in the intensive care unit and no neurological deficits or other complications were found. This case report aims to further discuss the importance and concerns regarding the perioperative management of craniotomy for clipping aneurysm.